Naturally Occurring Elettaria cardamomum Extract as a Corrosion Inhibitor for the Dissolution of Zinc in 1.0 M HCl. (14th November 2012) - Sobhi, M.
Abstract : The inhibitive action of water extract of naturally occurring Elettaria cardamomum plant against the corrosion of zinc in 1.0 M HCl solution was investigated using weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopy. From these measurements, it was found that the values of surface coverage ( θ ) and inhibition efficiency increase with increasing the concentration of the extracted compound. The activation energy of the corrosion was calculated and it was found that the presence of the extracted compound in 1.0 M HCl solutions increases the values of activation energy. The inhibiting effect of this extract results from its adsorption on the electrode surface via the adsorption centers of the compounds present in the extract. The adsorption of this extract compound onto the surface of zinc follows the Langmuir adsorption isotherm. The thermodynamic parameters were calculated for the tested system from the data obtained at different temperatures.